PJMHS 2023
DOI: 10.53350/pjmhs202317221
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Microorganisms in High Vaginal Swabs Obtained from women in OPD presenting with Vaginal Discharge

Abstract: Background: After menstrual irregularities, second common gynecological problem is vaginal discharge. Change in dynamic ecosystem of vaginal flora can cause the overgrowth of pathological microorganism that creates vaginal discharge. Owing to syndromic approach in low income countries, the identification of specific causative organism is masked. Aim: To determine the frequency of various micro-organism in high vaginal swab obtained from women in outpatient department presenting with vaginal discharge. Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…VVC is believed to be the second common cause of vaginal discharge only after bacterial vaginosis. 31,32 Although it is believed that Candida albicans which is a dimorphic opportunistic fungal pathogen is involved in most of the VVC infections, there is also increasing evidence of non albicans causing VVC. A study made in the year 2019 on the population of pregnant women reported VVC prevalence of 36.5%.…”
Section: Discussionmentioning
confidence: 99%
“…VVC is believed to be the second common cause of vaginal discharge only after bacterial vaginosis. 31,32 Although it is believed that Candida albicans which is a dimorphic opportunistic fungal pathogen is involved in most of the VVC infections, there is also increasing evidence of non albicans causing VVC. A study made in the year 2019 on the population of pregnant women reported VVC prevalence of 36.5%.…”
Section: Discussionmentioning
confidence: 99%